Opinion: Peritoneal Dialysis In Pakistan: An Insider’s View. State of Affairs and Planning? - Qayyum, Ahad (Pakistan Journal of Kidney Diseases, 2021)
Pakistan has an estimated population of 212 million while the incidence of end stage renal disease in Pakistan is 100 patients per million; hence approximately 22,000 patients require maintenance dialysis to sustain life in our country. Remarkably peritoneal dialysis (PD) as a form of maintenance renal replacement is utilized in less than one per cent of these patients. In the absence of a formal dialysis registry, we place the total number of chronic ambulatory peritoneal dialysis patients (CAPD) in Pakistan at approximately 76 excluding holiday patients who are visiting from abroad (*This figure was estimated by enquiring the total number of patients each PD units care in Pakistan. This figure was corroborated with the sole distributor of CAPD fluids in Pakistan.).